2017
DOI: 10.18203/2320-6012.ijrms20173017
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections among men who have sex with men: a retrospective study in a tertiary care hospital

Abstract: Background: Men who have sex with Men (MSM) have a higher prevalence of HIV and other sexually transmitted infections (STI) than the heterosexual men. In India, NACP recommendations to reduce HIV prevalence among MSM include early detection of HIV and other STI by screening and treatment. We conducted a study of STIs among MSM attending our OPD. The aim of the study was to assess the prevalence of STIs in MSM attending our OPD.Methods: 1215 MSM among 9008 patients who attended our OPD between June 2015 and May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Although it represents the cornerstone of STI prevention, condom use was still inconsistent in a large proportion of our population. This finding confirms the results of other studies, and reflects a lack of awareness of the risks associated with unprotected sex [19]. Having multiple sexual partners is common in the MSM community, and still many do not use condoms consistently.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although it represents the cornerstone of STI prevention, condom use was still inconsistent in a large proportion of our population. This finding confirms the results of other studies, and reflects a lack of awareness of the risks associated with unprotected sex [19]. Having multiple sexual partners is common in the MSM community, and still many do not use condoms consistently.…”
Section: Discussionsupporting
confidence: 89%
“…Having multiple sexual partners is common in the MSM community, and still many do not use condoms consistently. Recent data indicated that less than 60% of MSM reported using a condom [18]genotype distribution, intraepithelial neoplasia (AIN, and evidence of a limited use of condoms emerged from another study too [19]. One of the reasons for this situation lies in that “safer sex” campaigns have lost traction in this population.…”
Section: Discussionmentioning
confidence: 99%